Effect of Selective Serotonin Reuptake Inhibitors and Immunomodulator on Cytokines Levels: An Alternative Therapy for Patients with Major Depressive Disorder. (17th November 2013) - Hernandez, María Eugenia; Mendieta, Danelia; Pérez-Tapia, Mayra; Bojalil, Rafael; Estrada-Garcia, Iris; Estrada-Parra, Sergio; Pavón, Lenin
Abstract : Major depressive disorder (MDD) is a psychiatric illness that presents as a deficit of serotonergic neurotransmission in the central nervous system. MDD patients also experience alterations in cortisol and cytokines levels. Treatment with selective serotonin reuptake inhibitors (SSRIs) is the first-line antidepressant regimen for MDD. The aim of this study was to determine the effect of a combination of SSRIs and an immunomodulator—human dialyzable leukocyte extract (hDLE)—on cortisol and cytokines levels. Patients received SSRIs or SSRIs plus hDLE. The proinflammatory cytokines IL-1 β, IL-2, and IFN- γ ; anti-inflammatory cytokines IL-13 and IL-10; and 24-h urine cortisol were measured at weeks (W) 0, 5, 20, 36, and 52 of treatment. The reduction in cortisol levels in the SSRI-treated group was 30% until W52, in contrast, the combined treatment induced a 54% decrease at W36. The decline in cortisol in patients who were treated with SSRI plus hDLE correlated with reduction of anti-inflammatory cytokines and increases levels of proinflammatory cytokines at the study conclusion. These results suggest that the immune-stimulating activity of hDLE, in combination with SSRIs, restored the pro- and anti-inflammatory cytokine balance and cortisol levels in depressed patients versus those who were given SSRIs alone.